Peran Tutor Dalam Meningkatkan Minat Baca Warga Belajar Program Paket B di Lembaga Pemasyarakatan Kelas II A Kota Samarinda - Neni Sofianita Amalia; Saraka M. Ali; Sri Wahyuni (Jurnal Riset Sosial Humaniora dan Pendidikan, 2024)
This research aims to describe the role of tutors in increasing the reading interest of residents studying the Package B program at the Class II A Correctional Institution in Samarinda. The subject of this research was obtained from the results of data collection in the form of interviews, observation and documentation. This research uses descriptive research methods with a qualitative approach. Data sources in this research include the PKBM chairman, tutors, and students studying at the Class II A Correctional Institution. The research location is on Jl. General Sudirman No. 15, Pasar Pagi Village, Samarinda Kota District. Meanwhile, data analysis techniques in this research use data collection, data reduction, data presentation and drawing conclusions. Triangulation was carried out to explain the validity of the data using source interviews and techniques. The results of the research show that: The role of tutors in increasing the reading interest of learning residents in the package B equality education program at the Class II A Correctional Institution for Learning Residents has fulfilled its role as seen from how the role of the teaching staff or tutor carries out its 4 roles, namely as informator, facilitator, motivator , and evaluators.